Unfavorable lipid profile and higher frequency of hot flashes during perimenopausal years after fallopian tube ligation. (June 2013) - Özkaya, Enis; Gokmen, Oya; Tosun, Alptekin; Kucuk, Emine; Baris, Songül; Korkmaz, Vakkas; Usta, Murat
Abstract Aim: We sought to study the effect of tubal ligation on lipid profile, ovarian reserve and hot flashes during perimenopausal years. Methods: A total of 210 perimenopausal women complaining of abnormal vaginal bleeding were enrolled for the study. Subjects' menstrual, reproductive and medical histories were recorded. Serum FSH, LH and estradiol levels were screened in all women to determine menopausal status. In order to rule out any gynecologic pathology, all subjects underwent transvaginal sonography. Women were divided into two groups according to presence (study group, n = 68) or absence (control group, n = 142) of tubal ligation history. Lipid profiles and ovarian reserve tests were compared between groups. Results: Mean age, parity, serum hemoglobin (Hb), high density lipoprotein (HDL-C), triglyceride, estradiol levels, endometrial thickness and frequency of hot flashes were significantly different between groups (p < 0.05). Mean age was 42.8 ± 1.9 years in women with tubal ligation and 45.9 ± 3.5 years in control group. Mean serum estradiol level was lower in group with tubal ligation (41.4 versus 92.5 pg/ml). Mean endometrial thickness was higher in control group (10.2 versus 7.5 mm). Age-adjusted serum Hb, HDL-C, triglyceride, estradiol, FSH level, endometrial thickness and frequency of hot flashes remained significantly different between groups (p < 0.05). Conclusion: Tubal ligation is associated with unfavorable lipid profile and higher frequency of hot flashes during perimenopausal years.